Kvartærgeologisk kartlegging og rekonstruksjon av isavsmeltinga i Grødalen, Sunndalsfjella - Vie, Even Hestad (The University of Bergen, 2012)
The thickness and extent of the inland ice during the Younger Dryas Chronozone (YD) in central parts of South-Norway is still debated. The aim of this thesis is to map the sediments in Grødalen, for reconstruction of the local deglaciation, and to put this into a regional setting. Grødalen is a fish-hook valley in Sunndalsfjella, Nordmøre, bordered by Dovrefjell to the south and Trollheimen to the north. Mapping based on aero photos has been done with supervision form the Geological Survey of Norway (NGU) in February 2011. The digitally sketched map was used as a basis for the field investigations. Core samples from Koksvikmyra were also collected for stratigraphic analyses and radiocarbon dating. Moraines in the mountains around Grødalen give evidence of a glacier advance that is older than the deposits in the valley. This is established as the Løstøl-fremmerdal Stage. Grødalen is featured by a typical dead ice landscape, including fan deposits and valley eskers. Distinct terraces characterize Grødalen and the adjacent valleys. These are elevated c. 760 m a. s. l., which corresponds to the valley threshold. They have earlier been interpreted as both lateral moraines and shore lines from a glacial dammed lake. Because of their morphology and texture, and the seeming lack of glaciolacustrine sediments in Grødalen, they are here interpreted as semisublateral drainage channels, controlled by the passage point in the valley. On the distal side of this passage point here is a sandur, on which there is observed ice wedge polygons. The sandur indicates that the glacier front has been situated at the passage point for some time. This stage is here established as the Grødalen Stage. The Vedde Ash was discovered in the core samples from Koksvikmyra. The basal sediments were dated to c. 12500 years BP, which indicates that Grødalen was deglaciated during the early YD. A simple reconstruction of the glacier surface shows that the Grødalen Stage can be synchronous or slightly older than the Giklingen deposit in Sunndalen. ...